National park userpays systems in Australia. Cost recovery vs access for all? - Hughes, Michael; Carlsen, Jack (Chinese Tourism Management Association, 2011)
This paper discusses the tension between user pays systems as a means of cost recovery and equity of public access using the example of Australian national parks. Six Australian state based national park management agencies were interviewed about their user pays systems. Australian national parks are managed as a public good, for biodiversity conservation, and to provide for recreation and tourism opportunities. Legislated social equity requirements result in discounted user pays systems that are generally not cost effective. This raises the question of whether user pays systems for cost recovery are compatible with access management based on social equity.